Comparative outcomes of different endovenous thermal ablation systems on great and small saphenous vein insufficiency: Long-term results - Robert A. Weiss (2018)
© 2015 Wiley Periodicals, Inc. Background and Objective: This study examined the outcomes of over a decade of endovenous thermal ablation (EVTA) treatments for great and small saphenous vein (GSV and SSV) insufficiency, utilizing three different endovenous thermal ablation systems. Materials and Methods: This retrospective study reviewed EVTA treatments performed at an outpatient clinic (MDLSVI) from April 1999 to February 2013. Systems included 810 nm diode (hemoglobin targeting), 1,320 nm laser (water targeting) and a radiofrequency (direct thermal transfer) (RF) device. Clinical and ultrasonographic evaluation were performed before treatment and at each follow-up visit. Patients were examined yearly by Duplex ultrasonography. Success was defined as complete absence of reflux. Results: Analysis of 934 treatments demonstrated that although recanalization could occur over time, endovenous ablation has a very high success rate. Ablation rates were 92.5%, 85.9%, and 71.9% at 6-months, 1-year, and 5-years after procedures. Recanalization occurred in 156 out of 934 treatments (16.7%) during the follow-up period. Among three difference systems, the total ablation success rate was significantly different (P < 0.001). The 1,320 nm Nd: YAG laser (n = 502) provided the highest ablation rate compared to the radiofrequency (n = 398) and 810 nm diode (n = 34) throughout their follow-up period, which were 8, 13, and 9 years, respectively. At 1-year follow-up, successful ablation rates of RF, 810 nm, and 1,320 nm were 78.2%, 80.8%, and 93.7%, respectively. At 5-year follow-up, successful ablation rates of RF, 810 nm, and 1,320 nm were 61.7%, 65.7%, and 84.7%, respectively. Conclusion: EVTA is very effective for ablation of the GSV and SSV. Complete ablation varied significantly among different systems with water targeting 1,320 nm providing the highest incidence saphenous vein ablation. This remained durable at 8-year follow-up by Duplex ultrasound.